2023
DOI: 10.1245/s10434-023-13468-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Hepatocellular Carcinoma Time to Treatment Initiation: A National Cancer Database Study

Abstract: Background The COVID-19 pandemic strained oncologic care access and delivery, yet little is known about how it impacted hepatocellular carcinoma (HCC) management. Our study sought to evaluate the annual effect of the COVID-19 pandemic on time to treatment initiation (TTI) for HCC. Methods The National Cancer Database was queried for patients diagnosed with clinical stages I–IV HCC (2017–2020). Patients were categorized based on their year of diagnosis as “Pre-COVID” (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Notably, the largest reduction was seen in bladder cancer care with a reduction of 6 days from diagnosis to radical cystectomy [23]. In contrast, two population-based HPB studies in The Netherlands and the United States found no reduction in time to treatment initiation [26,27]. In our cohort, the faster time to start of treatment for oncological patients during the pandemic is probably the result of the prioritization of oncological care in The Netherlands.…”
Section: Discussionmentioning
confidence: 52%
“…Notably, the largest reduction was seen in bladder cancer care with a reduction of 6 days from diagnosis to radical cystectomy [23]. In contrast, two population-based HPB studies in The Netherlands and the United States found no reduction in time to treatment initiation [26,27]. In our cohort, the faster time to start of treatment for oncological patients during the pandemic is probably the result of the prioritization of oncological care in The Netherlands.…”
Section: Discussionmentioning
confidence: 52%
“…There were also no significant differences in race between patients being evaluated for transplant versus those on a non-transplant treatment track. Additionally, it is well established that health insurance status is another barrier to receiving a liver transplant; particularly, patients without insurance or with Medicaid coverage have both delayed treatment and lower rates of treatment [ 28 , 29 ]. This patient population also exhibits a higher risk of death [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the direct effect of the viral infection, the rapid increase in patients with COVID-19 under limited resources has led to several governments and hospitals prioritizing management of patients and to delays in diagnosis and treatment of other diseases [7][8][9]. The severity of urgent diseases, regardless of COVID-19 infection, increased, with worse clinical outcomes during the COVID-19 pandemic relative to the severity in the prepandemic period [10][11][12], Moreover, the priority for treating malignancy was adjusted during the COVID-19 era as suggested by the World Health Organization that recommended postponement of nonurgent procedures, although malignancy is a life-threatening condition that may progress into an emergency situation [8].…”
Section: Introductionmentioning
confidence: 99%